A study of the causes leading to the liquidation of agricultural enterprises - Kotormán, Annamária (Applied Studies in Agribusiness and Commerce, 2009)
The viability of agricultural enterprises is of paramount importance. Their liquidation has harmful effects on broad strata of society. The aim of my research is therefore to analyze the leading causes of liquidation of agricultural enterprises. The research was led on 17 agricultural enterprises. This may help in the prevention and treatment of their insolvency. The research results show that a long-term agricultural production is not sustainable with a low equity capital. For the long-term maintenance it is necessary that the investors establish the enterprise with a capital according to the type of the production.The loan can not replacethe entrepreneursown resources,it is only complementaryto it.Theownersof agriculturalbusinessesshould strive to ensurethatthe paid-up share capital is kept in the firm, because in case of payment difficulties, this can be an adequate financial provision. Companies with financial problems can avoid liquidation if the crisis is detected in time by the leaders. However, the owners must organize the management of the enterprise so that it should have the necessary technical and economic knowledge. With an appropriate management, and use of means of crisis management, the liquidation of the enterprise can be prevented.